Evaluating the effectiveness of in situ characterization techniques in overcoming mechanistic limitations in lithium–sulfur batteries. Issue 4 (3rd March 2022) - Rehman, Sarish; Pope, Michael; Tao, Shanwen; McCalla, Eric
Abstract : Li–S batteries hold great promise for electric vehicles but complex reaction mechanisms during operation have, to date, prevented commercialization. In situ techniques provide insights that may overcome these limitations. Abstract : Advanced energy storage systems require high energy and power densities, abundant availability of raw materials, low cost, reasonable safety, and environmental benignancy. Owing to their exceptionally high theoretical gravimetric energy density (2600 W h kg −1 ) and specific capacity (1675 mA h g −1 ), lithium sulfur batteries (LSBs) are considered a promising candidate for next-generation energy storage systems. However, low sulfur loading, rapid capacity depletion, poor coulombic efficiency, and unstable cyclability have so far prevented their commercialization. These issues mainly originate from the lack of knowledge about the mechanisms taking place during the redox reactions involved in the complex conversion chemistry that LSBs rely on. In situ characterization techniques have long been sought to help answer questions regarding these mechanisms. Herein, we review the major advancements in the field of LSBs with a particular focus on the role of in situ methodology. In situ methods often require adapted cell designs and significant resources to achieve useful results. It is, therefore, an opportune time to take stock as to what advancements have been made in LSBs thanks to in situ methods, where all previous ex situ methods have failed. The important details regarding implementing in situ characterization techniques to properly understand the mechanisms of LSBs are discussed, as are the major challenges associated with these methods. Finally, future perspectives regarding viable commercial LSBs are presented.